Conceptualisations of Citizenship among Educational Stakeholders in Newly Independent Madagascar - Ellen Vea Rosnes; Helihanta Rajaonarison (Revista de História da Sociedade e da Cultura)
After independence from France in 1960, there were different views on how to educate newly independent Malagasy citizens. This article asks what kinds of citizenship was to be promoted and to whom should Malagasies learn to be loyal as citizens of their village, the newly independent nation, and a global world. Through a framework for critical citizenship education and perspectives on citizenship and transloyalities, this article analyses national, international, public, and private (religious) conceptualizations of citizenship education post-independence. The analysis is based on four reports: a 1960 Protestant conference report, a 1963 UNESCO mission report, a government document from 1964, and a 1968 report from a student organization conference. The analysis reveals that different stakeholders within newly independent Malagasy education promoted different conceptualizations of citizenship, some more critical than others.